Ensino investigativo de evolução por meio de variantes virais - Túlio Henrique Lemos (2024)
Evolution is the cornerstone of biology teaching, due to the interconnection it has with the all the content that it is taught in the area of Natural Sciences, which is in accordance with the Brazilian National Common Core Curriculum, known as the Base Nacional Comum Curricular. However, it is still little explored and valued in Basic Education; its teaching is, many times, decontextualized from other contents in biology and from the teaching-learning process, especially inquiry-based science teaching, which is highlighted by eliciting students to be interested as well as stimulating them to speak, to think, to create, and to listen. Thus, this study aimed to develop an Investigative Teaching Sequence addressing the teaching of Evolution contextualized to Virology, making use of a case study about the emergence of virus variants. The present study was observational with a qualitative approach. Moreover, as one of its stages, the contextualization approach between Evolution and Virology was analyzed in brazilian textbooks of Natural Sciences approved by the Programa Nacional do Livro e do Material Didático [National Program of the Textbook], by means of a documentary analysis. The Investigative Teaching Sequence was conducted with 40 high school students from a state-funded public school of Belo Horizonte (MG) and the data collected was analyzed through the Content Analysis method. As a result, protagonism, hypothesis construction, collective elaboration of conclusions, and the production materials for scientific divulgation from the results found by them were all features observed in the students. It was discovered that, out of the seven textbook collections analyzed, only one of them presented contextualization between the contents of Evolution and Virology. The study ended with the production of a Investigative Teaching Sequence, improved in relation to the sequence taught to the students, which proved to be effective in the assimilation of key concepts of Evolution related to the evolutionary mechanisms. The product is a resource so that teachers can use inquiry-based science teaching of Evolution contextualized to Virology with high school students. In addition, a reflection is presented so that textbook publishers and authors can reassess the contextualization of contents of biology addressed in their textbooks.